2003
DOI: 10.1128/iai.71.5.2341-2349.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitric Oxide onPseudomonas aeruginosaInfection of Epithelial Cells from a Human Respiratory Cell Line Derived from a Patient with Cystic Fibrosis

Abstract: Cystic fibrosis (CF) is characterized by airway inflammation and chronic bacterial lung infection, most commonly with Pseudomonas aeruginosa, an opportunistic human pathogen. Despite the persistent airway inflammation observed in patients with CF, although phagocyte inducible nitric oxide synthase (iNOS) production is upregulated, expression of iNOS in the respiratory epithelium is markedly reduced. Given the antimicrobial action of NO, this may contribute to the chronic airway infection of this disease. To de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
65
2
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 54 publications
3
65
2
1
Order By: Relevance
“…It is intriguing that arginine serves as the substrate of nitric oxide synthetase for the synthesis of an important second messenger molecule, NO (21). Perhaps maintaining such a sophisticated arginine metabolic network in P. aeruginosa provides this opportunistic human pathogen an advantage in establishing infections, such as in cystic fibrosis patients (5).…”
Section: Discussionmentioning
confidence: 99%
“…It is intriguing that arginine serves as the substrate of nitric oxide synthetase for the synthesis of an important second messenger molecule, NO (21). Perhaps maintaining such a sophisticated arginine metabolic network in P. aeruginosa provides this opportunistic human pathogen an advantage in establishing infections, such as in cystic fibrosis patients (5).…”
Section: Discussionmentioning
confidence: 99%
“…84 NO has important local effects in vasodilatation as well as direct anti-bacterial activities. 85,86 Studies in iNOS deficient mice have shown an anti-inflammatory role for NO. The lack of iNOS induced a significant increase in leukocyte rolling and neutrophil recruitment to the lungs.…”
Section: Airway Epithelial Cell Responses To Bacteriamentioning
confidence: 99%
“…Bacterial killing activity could be restored in airway epithelial cells derived from a patient with cystic fibrosis, which have reduced expression of iNOS, by transfection with human iNOS cDNA. 85 Excessive NO production due to bacterial and cytokine induction of iNOS, however, is a major cause of lung injury. Nitrosylation by nitric oxide compounds such as peroxynitrite formed with reactive oxygen species in the proximity of activated neutrophils, can cause cell necrosis by disruption of mitochondrial metabolism and enhance apoptosis by inhibition of the anti-apoptotic transcription factor NF-kB.…”
Section: Airway Epithelial Cell Responses To Bacteriamentioning
confidence: 99%
“…Indeed, elevated concentrations of exhaled NO and increased epithelial expression of NOS2 are characteristic features of chronic inflammatory airway diseases such as asthma (1,2). The biological roles of NOS2 within the airway epithelium include contribution to innate host defense (3,4), regulation of epithelial ion transport (5), and maintenance of epithelial barrier integrity (1,6,7). In addition, our recent studies showed that physiological concentrations of NO can promote airway epithelial cell migration and repair in response to in vitro injury, which was associated with increased expression and activation of gelatinase B (matrix metalloproteinase-9; MMP-9) (8).…”
mentioning
confidence: 99%